A case of panspinal epidural abscess that presented with meningeal irritation. Issue 3 (6th July 2017) - Okada, Naoki; Nishiyama, Takashi; Kurihara, Maki; Nishimura, Yusuke; Nishimura, Yoshiro; Ando, Yukihiro; Otsubo, Saori; Yamada, Katsumi; Maeda, Yuji
Abstract : Case: In rare cases, spinal epidural abscess involves the entire spine and can lead to neurological deficits and sepsis if treatment is delayed or suboptimal. A 65‐year‐old man was admitted with a diagnosis of bacterial meningitis. After admission, magnetic resonance imaging showed a spinal epidural abscess from the cervical to lumbar spine. Blood culture revealed Staphylococcus aureus . The patient was initially treated medically because he had no neurological deficits. Repeat blood culture remained positive and abscesses were found in the mediastinum and bilateral psoas muscles. Outcome: Surgery was carried out and the patient's postoperative course was satisfactory. Conclusion: Spinal epidural abscess can extensively affect the spine and may present with the symptoms of bacterial meningitis. It is essential to examine the entire spine and paraspinal regions and to treat early in cases of spinal epidural abscess. Abstract : Spinal epidural abscess can extensively affect the spine and may present with the symptom of bacterial meningitis. Examining the whole spine and paraspinal abscesses is essential in cases of spinal epidural abscess.